Thermosensitive Structural Changes and Adsorption Properties of Zeolitic Imidazolate Framework-8 (ZIF-8) - Lee, Taehee; Kim, Hyungmin; Cho, Woosuk; Han, Doug-Young; Ridwan, Muhammad; Yoon, Chang Won; Lee, Jong Suk; Choi, Nakwon; Ha, Kyoung-Su; Yip, Alex C. K.; Choi, Jungkyu (American Chemical Society, 2015)
We compared four types of ZIF-8 with varying sizes and shapes to determine their thermal-structural stability and derive appropriate thermal activation conditions and correlation between structural characteristics and adsorption properties. Under air, the ZIF-8 phase for all the samples was converted completely into the zinc oxide phase above similar to 300 degrees C, though thermalgravimetric analysis (TGA) indicated that the original structure was stable to similar to 300-350 degrees C. Longer exposures (similar to 30 d) suggested that thermal activation at similar to 200 degrees C was appropriate for the removal of guest and/or solvent molecules under air without structural damage. Despite no noticeable change in X-ray diffraction (XRD) patterns after activation at 250 degrees C under air, the resulting BET surface areas and CO2 adsorption amounts (at 1 bar and 30 degrees C) of ZIF-8s were reduced to similar to 44-54 and similar to 72-87%, respectively, as compared to those of appropriately activated ZIF-8s. It appears that after the activation at 250 degrees C under air, some Zn and N atoms were dissociated and converted to ZnOH and NOH, respectively, causing the partial structural damage of ZIF-8s.
Keywords: MOLECULAR-SIEVE MEMBRANE; METAL-ORGANIC FRAMEWORKS; IN-SITU SYNTHESIS; CO2 ADSORPTION; SEPARATION; PURIFICATION; STABILITY; FUNCTIONALITY; ENHANCEMENT; TEMPERATURE